Towards blockchain led decentralized autonomous organization (DAO) business model innovations - Saurabh, Kumar; Rani, Neelam; Upadhyay, Parijat (Benchmarking : an international journal, 2023)
PurposeToday, business model innovations leverage digital technologies to gain a competitive advantage and transform business processes. Blockchain is still gaining attention in specific fields and bringing value to business models. There is a dearth of research on how blockchain decentralized autonomous organizations impact organization business model innovations. This study attempts to contribute the body of knowledge based on a review of decentralized autonomous organizations and the business model innovation literature using the integrative and generative approach.Design/methodology/approachThe paper offers an analysis of decentralized autonomous organizations based on digital business models built on the well-established work by Osterwalder and Pigneur (2010). The practical multilayered decentralized autonomous organizations architectural implementation model design is achieved using practical archetypes depicted in the proposed decentralized autonomous organizations business model. The paper evaluates a marketplace comprising 13 decentralized autonomous organizations led platforms with core functionalities.FindingsThe paper delivers decentralized autonomous organizations led digital business model canvas elements to explain decentralized autonomous organization business model innovations. It presents the underlying multilayered decentralized autonomous organizations architectural implementation model required to conceptualize a practical business model with an enterprise-ready target operating model.Research limitations/implicationsThe paper contributes directly to the practical decentralized autonomous organizations business model canvas, exemplifying the nine elements of decentralized autonomous organizations’ characteristics for any organizational transformation. The tools and accelerators (business model, layered architecture, target operating model and product mapping) developed in the paper address the managerial challenges of redesigning the decentralized business models.Originality/valueThe proposed decentralized autonomous organizations smart contract powered business model provide a digital platform to adhere to rules, follow policies, preserve principles and develop consensus without human interventions. The paper shapes the first of its kind decentralized autonomous organizations marketplace evaluation while mapping it to decentralized autonomous organizations layered architecture product requirement considering business model dimension to adopt actionable target operating model.